Pemodelan Sistem Dinamis Analisis Daya Dukung Pencemaran Air Sungai Batang Arau Di Kota Padang - Lisa Rahayu; Indang Dewata; Nurhasan Syah; Iswandi Umar (Jurnal Penelitian Pendidikan IPA, 2025)
The Batang Arau River in Padang City exhibits contrasting environmental conditions between its upstream and downstream segments. The upstream–midstream areas still maintain good water quality with positive carrying capacity, while the downstream segment has exceeded its natural assimilation limit due to increasing pollutant loads originating from domestic and community activities. This study aims to analyze water quality, calculate carrying capacity, and model the relationship between community behavior and the river’s assimilation capacity using a system dynamics approach. The modeling results indicate a continuous decline in carrying capacity driven by population growth and waste generation, illustrating that human behavior has a direct impact on the ecological balance of the river. Therefore, sustaining the ecological function of the Batang Arau River requires integrated pollution control policies, community-based waste management, and continuous environmental education to enhance public awareness and ensure the long-term sustainability of the river ecosystem.